Deterministric models of active magnetic bearing system - Husain, Abdul Rashid; Ahmad, Mohamad Noh; Mohamed Yatim, Abdul Halim (Academy Publisher, 2007)
In this paper the development of mathematical model of voltage-input and current-input active magnetic bearing (AMB) system in deterministic form is presented. The AMB system, which is open-loop unstable and highly coupled due to nonlinearities inherited in the system such as gyroscopic effect and mass imbalance, requires a dynamic controller that can stabilize the system. In order to synthesize the controller, the nonlinear AMB model is transformed into its deterministic form by using the known upper and lower bounds of the parameters and the state variables of the system. The voltage-input AMB model shows that the system contains mismatched uncertainty and non-zero system states value which suggests that synthesizing nonlinear dynamic controller for this model is almost unfeasible. Overcoming these problems, the currentinput AMB model, however, is in the structure that is more suitable for the design of a stabilizing controller. A result from a computer simulation work shows that the states of the system behave nonlinearly without feedback control; however, this final system model with its numerical values can be used for the design of a class of a dynamic controller for system stabilization.